'Auto‐supercharge' of the anterolateral thigh flap during the reconstruction of lower extremity defects: A turbocharge technique for flow‐through flaps. Issue 2 (May 2014) - Yildiz, Kemalettin; Duygu, Cetin; Akkus, Ali M.; Karaaltin, Mehmet V.; Kayan, Resit B.; Guneren, Ethem
<x xml:space="preserve">Abstract</x> Aim The anterolateral thigh flap is a workhorse perforator flap option that can be used as a flow‐through flap in the reconstruction of defects with vascular insufficiency. In the present study, the flow‐through concept was introduced in terms of preserving blood inflow of the flap and establishing blood flow to the distal portion of the flap as a supercharge technique. Patients and Methods A 43‐year‐old male patient suffered from a diabetic foot. After precise wound debridements and infection control, free anterolateral thigh flap was planned for reconstruction. There were two perforators: one musculocutaneous perforator based on the descending branch of the lateral circumflex femoral artery (LCFA) entering proximally into the flap, and the second a septocutaneous perforator based on the deep femoral artery branch that perfuses the distal aspect of the flap. We observed that the distal portion of flap became compromised when we clamped the second perforator. Therefore, the second perforator was divided from the deep femoral truncus, traced to the distal end of the LCFA and anastomosed to it in an end‐to‐end fashion. Thus, an auto‐supercharge procedure was performed. Results Wound healing was uneventful. There was no total or partial flap necrosis at the 12‐month follow up. Conclusion Auto‐supercharging augments the flap circulation and relieves flap congestion. Thus, it expands the indications for flow‐through flaps in revascularisation and flap salvage.